Fenomenologi Agama - Mutaqin, Nurul (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Abstract Evolutionary thinking about religion generally explains the scientific information contained in a religion, both about how the religion came to be, as well as how a researcher tries to dissect the religion according to historical principles and identify it with several options which involve progress between religious space and time with human reality with various patterns and ways of thinking. This possibility raises prejudices about religion which in fact is a journey from animism, belief in spirits which are the root of religion, ascetic entities, etc. Trying to explore it as a phenomenology when religion is confronted with real life which prioritizes intellectuals, science and technology. The approach taken to reconcile religion and intellectuals, namely by respecting each other, and not exceeding each other's authority, so that the prejudice of assimilation does not extend to the understanding of the formation of a new religion, but rather to the substantial understanding that already exists in religion. Keywords: Phenomenology, Religion